Politik Hukum Sertifikasi Halal Sebagai Instrumen Penguatan Ekonomi Syariah Nasional - Miftakhul Huda (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
This research aims to analyze the legal politics of halal certification as a strategic instrument in strengthening the national sharia economy in Indonesia. Halal certification is no longer seen simply as fulfilling normative religious obligations, but has developed into a state legal policy that functions to provide legal certainty, consumer protection, and increase the competitiveness of national products in domestic and global markets. Through Law Number 33 of 2014 concerning Halal Product Guarantees and its derivative regulations, the state emphasizes the legal political direction that places halal as part of national economic development, especially in supporting the halal industry, micro, small and medium enterprises, as well as expanding exports of sharia-based products. The implementation of the mandatory halal policy which has been extended until 2026 increasingly shows that halal certification is a legal instrument that has religious, economic and strategic dimensions in strengthening Indonesia's sharia economic ecosystem. This research uses normative juridical methods with legislative, conceptual and public policy approaches. The research results show that the legal politics of halal certification are directed at three main objectives, namely protecting the rights of Muslim consumers, increasing market confidence, and strengthening Indonesia's position as the center of the global halal industry. This policy also has implications for improving business governance that is more transparent, accountable and in accordance with maqashid sharia principles, especially in protecting religion (hifz al-din) and property (hifz al-mal). Thus, halal certification has a strategic function as a social and economic engineering instrument capable of encouraging sustainable national sharia economic growth.